TRANSFORMATIONAL TRENDS IN THE DEVELOPMENT OF PARTY SYSTEMS AMID POLITICAL TURBULENCE AND THE STRUCTURAL CRISIS OF REPRESENTATIVE DEMOCRACY - Zgurska, Valentyna; Baieva, Yuliia (Public Management and Policy, 2026)
In the article, we study the evolution of party systems in the period of modern political turbulence, accompanied by crisis phenomena of representative democracy, the growth of political polarization and the spread of the ideology of populism. The purpose of the article is to theoretically analyze the features of the evolution of party systems in conditions of political turbulence and crises of representative democracy. The article uses general scientific research methods, in particular analysis, systems approach, comparison, etc. Theoretical approaches to the analysis of party systems formulated in classical studies of political science are considered. It is determined that electoral volatility, fragmentation of the political space and a decrease in the level of trust in traditional party institutions are important indicators of the transformation of party systems. It is proven that in the 21st century, representative democracy is experiencing a complex crisis of legitimacy, which is manifested in the growing distance between citizens and political elites, the weakening of the social basis of traditional parties, and the spread of populism. The article emphasizes that populist parties actively use anti-elitist rhetoric, appeals to national identity, and emotional narratives, which allow them to mobilize voters in periods of economic and social instability. It is proven that in conditions of global political turbulence, the crisis of representative democracy acquires a systemic character and creates the prerequisites for the transformation of party systems. It is revealed that the key factors of such transformations are global socio-economic crises, international military conflicts, and the development of the information society and artificial intelligence technologies, which enhance the possibilities of using populism in the mobilization of the electorate.